Students and teenagers as perpetrators of robbery in Indonesia from the perspective of law enforcement - Rusmana, I Putu Edi (Journal of Law Science, 2024)
Students are a group of teenagers who are the next generation of the nation. A person in his adolescence is someone who is looking for his identity by socializing with peers, paying attention to the surrounding environment, exploring something that has never been done, sometimes this can make a teenager fall into criminal acts. The criminal act that is currently rampant among teenagers who are still students is theft with violence carried out on the street or commonly called mugging, therefore it is necessary to know the factors that drive a student to commit mugging and law enforcement so that a teenager who is still a student can avoid it. This research is normative based on primary, secondary and tertiary legal sources contained in expert doctrine, sources from previous research and laws or books. This study concludes that there are factors that can influence teenagers to commit mugging such as economic, educational, environmental, sociological, psychological and biological factors. In its enforcement there are two law enforcement efforts, namely preventive efforts and repressive efforts. It is hoped that this research can be a reference so that crimes that are not repeated again.